Analisis Pengaruh Kompensasi Dan Lingkungan Terhadap Motivasi Kerja Karyawan (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to determine the effect of compensation and the environment simultaneously on employee motivation at CV. Nuri City of Tasikmalaya. The effect of organizational culture and job satisfaction partially on employee performance at CV. SPP Corporation. The method used in this research is quantitative with a survey approach. With a research sample of 40 people as respondents to CV. Nuri City of Tasikmalaya based on 40 known population data. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. The results of simultaneous testing of compensation and the environment have a significant effect on employee motivation The results of partial testing of compensation variables have a significant effect on employee motivation, as well as environmental variables that have a partial significant effect on employee motivation.